(untitled) (Journal of Educational Sciences, 2018)
The article examines the problem of researching the state of readiness of highly skilled oarsmen in the pre-competition stage and the competitive period. The study is aimed at comparing the studied conditions in oarsmen. The main of them we chose the need for communication, inner well-being, external activity and sportive attitude. The solution of this problem can be realized with a comprehensive study and the ability to manage the conditions of oarsmen in their preparation and performances in competitions. Rowers with high levels of preparedness are more likely to perform predictable results. We consider the readiness status of oarsmen specializing in kayak and canoe, with different typological properties. Diagnostics of the level of their condition in the period of responsible competitions will allow creating typological standards intended for assessing the condition of the oarsmen’s organism. Key words: optimization, pre-statistical readiness, highly qualified sticks, kayaks, canoe, pre-competition stage, competition period.